PHYTOCHEMICAL AND ANTISICKLING ACTIVITIES OF TERMINALIA CATAPPA (COMBRETACEAE) LEAF EXTRACTS - Samuel, B.; Okogun, J.; Idowu, K.; Olaniyi, A. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Ethno botanical survey revealed that the dried fallen leaves of Terminalia catappa Linn. are used locally in various parts of Nigeria for the management of sickle cell anaemia. This research investigated if Terminalia catappa leaf interferes with the basic mechanism of erythrocyte sickling and the group of compounds responsible for its antisickling activity were identified and characterized. Bioactivity guided fractionation of the methanolic extract showed that the highest antisickling activity, in the erythrocyte sickling model, resided in its triterpenoids components (fraction F3, K = 0.0037 min-1). This fraction drastically reduced the rate of erythrocyte sickling and is very significantly more active than the control and other active fractions F1 and F2 (P<0.001, 1-way ANOVA, Tukey’s Multiple Comparison test). The antisickling effect is concentration dependent. Graded dose response showed that 0.75mg/ml is the optimal concentration for in vitro bioassay method (P>0.05). Bioactivity guided separation of the extract was carried out on flash chromatography using RP18 and Silica gel stationary phases respectively. Final separation was done by HPLC on Cyanosilica column. Structural elucidation was by use of Nuclear magnetic resonance (NMR) and mass spectrometry (MS). The most active components were established to be two triterpenic acids (1) 2Î±, 3Î², 24-trihydroxy-12-ursen –28-oic acid(2), 2Î±, 3 Î², 24 – trihydroxy – 12, 20(30) – ursa-dien-28-oic acid work shows that there is a scientific basis for the application of this extract in the management of sickle cell anaemia in traditional medicine. Acknowledgements: NIPRD & TRENTO University provided funding